2020
DOI: 10.1371/journal.pone.0242100
|View full text |Cite
|
Sign up to set email alerts
|

Pessimistic dairy calves are more vulnerable to pain-induced anhedonia

Abstract: Pain induces deficits in appreciation of rewards (i.e. anhedonia) and variation in response to pain may be partly explained by individual differences in general expectations (i.e. optimism). Dairy calves are routinely subjected to painful procedures such as hot-iron disbudding. We tested if female Holstein calves (n = 17) display signs of anhedonia (as evidenced by reduced consumption of a sweet solution) after hot-iron disbudding (performed under general and local anesthesia), and whether individual differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Whether captive animals experience depressive-like states is attracting more attention [ 38 ] and recent work provides some evidence of anhedonia-like responses in farm species. For instance, pain due to hot-iron disbudding in dairy calves was associated with reduced time spent playing [ 39 ], decreased motivation for milk [ 40 ], and reduced consumption of a sweet solution [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether captive animals experience depressive-like states is attracting more attention [ 38 ] and recent work provides some evidence of anhedonia-like responses in farm species. For instance, pain due to hot-iron disbudding in dairy calves was associated with reduced time spent playing [ 39 ], decreased motivation for milk [ 40 ], and reduced consumption of a sweet solution [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, behavioral response and the reported experience of pain to similar noxious stimuli is influenced by various factors including social context ( Koban and Wager, 2016 ), culture, education, stoicism, personality, sex, and environmental circumstances ( Linton and Shaw, 2011 ). Similarly, it has been shown that expression of pain in animals differs depending on a number of influences, including temperament ( Ijichi et al, 2014 ), affective state ( Lecorps et al, 2020 ) and social interactions ( Guesgen et al, 2014 ). This variability among individuals can lead to difficulty interpreting and comparing the experience of pain from a specific noxious insult across a group of animals.…”
Section: Measuring Pain In Livestockmentioning
confidence: 99%
“…These measures can be insensitive, often discount the long-term effects of pain, and overlook the cognitive and psychological components of pain ( Weary et al, 2006 ; Steagall et al, 2021 ; Tschoner, 2021 ). More recently, the psychological and affective state elements of pain in livestock have been studied to assess the changes in cognition, motivation and decision-making that are known to occur due to higher-order processing of nociceptive signals ( Neave et al, 2013 ; Sneddon et al, 2014 ; Adcock and Tucker, 2020a ; Lecorps et al, 2020 ; Kleinhenz et al, 2021 ).…”
Section: Measuring Pain In Livestockmentioning
confidence: 99%
“…A more inclusive set of descriptors would be applicable to nonhuman and human species. Cognitive and social features of pain are recognized in mammalian species, including investigations in rodents 23,24 and other domesticated species 25 . The capacity to communicate pain to conspecifics and others is well‐demonstrated with development of measures of facial grimaces during pain in nonhuman animals, with social parameters important as these expressions vary with the social context 26‐28 .…”
Section: Phylogenetic and Ontogenetic Perspectives On Pain Complexitymentioning
confidence: 99%
“…A more inclusive set of descriptors would be applicable to nonhuman and human species. Cognitive and social features of pain are recognized in mammalian species, including investigations in rodents 23,24 and other domesticated species 25 .…”
Section: Phylog Ene Ti C and Ontog Ene Ti C Per S Pec Tive S On Pain ...mentioning
confidence: 99%